Evaluation of the impact of social dysfunctions on hidden cost-performance. Case of a Moroccan banking institution - Mohamed , BRIACHE; NAFZAOUI, Mohamed Achraf (Revue du contrôle, de la comptabilité et de l’audit, 2026)
The purpose of this paper is to highlight the adaptability of the socio-economic diagnostic process, as a revealer of organizational social dysfunctions, to the specific characteristics of the Moroccan banking sector. It shows to which degree the socio-economic analysis model, through its processual axis based on the identification and measurement of hidden costs, can contribute to improve performance. The first part presents the socio-economic theory developed by Savall, as well as the concept of hidden costs, defined as costs that originate in phenomena usually not taken into account by official accounting systems. The second part highlights the results of a case study conducted in a banking institution that manages a staff of 2181 persons. These results revealed about ten types of social dysfunctions that generate two types of hidden costs: overhead and non-production. They are estimated at more than 30 million dirhams, or 15,000 dirhams per person, except that they no longer appear in the summary accounting statements. This should enlighten the banking leaders on the content of the corrective actions to be taken, requiring to put the human capital at the center of these actions to improve their working conditions.